Source apportionment of PM2.5 at two Seattle chemical speciation sites. (2nd July 2020) - Friedman, Beth
ABSTRACT: Positive Matrix Factorization analysis of PM2.5 chemical speciation data collected from 2015–2017 at Washington State Department of Ecology's urban NCore (Beacon Hill) and near-road (10th and Weller) sites found similar PM2.5 sources at both sites. Identified factors were associated with gasoline exhaust, diesel exhaust, aged and fresh sea salt, crustal, nitrate-rich, sulfur-rich, unidentified urban, zinc-rich, residual fuel oil, and wood smoke. Factors associated with vehicle emissions were the highest contributing sources at both sites. Gasoline exhaust emissions comprised 26% and 21% of identified sources at Beacon Hill and 10th and Weller, respectively. Diesel exhaust emissions comprised 29% of identified sources at 10th and Weller but only 3% of identified sources at Beacon Hill. Correlation of the diesel exhaust factor with measured concentrations of black carbon and nitrogen oxides at 10th and Weller suggests a method to predict PM2.5 from diesel exhaust without a full chemical speciation analysis. While most PM2.5 sources exhibit minimal change over time, primary PM2.5 from gasoline emissions is increasing on average 0.18 µg m −3 per year in Seattle. Implications: This study utilizes Positive Matrix Factorization to determine PM2.5 sources from chemical speciation measurements at two urban Seattle sites from 2015-2017. The paper reports PM2.5 source trends, and extends previous source apportionment analyses in Seattle to the present day. The study also quantifies diesel PM2.5 at a near-road site, and describes a predictive model that allows estimation of the contribution of diesel PM2.5 to the total measured PM2.5 at near-road sites across the country without a full chemical speciation analysis.